Financial interests of patient organisations contributing to technology assessment at England's National Institute for Health and Care Excellence: policy review. (16th January 2019) - Mandeville, Kate L; Barker, Rosie; Packham, Alice; Sowerby, Charlotte; Yarrow, Kielan; Patrick, Hannah
Abstract: Objective: To investigate the prevalence of financial interests among patient organisations contributing to health technology assessment at the National Institute for Health and Care Excellence (NICE) in England and the extent to which NICE's disclosure policy ensures that decision making committees are aware of these interests. Design: Policy review using accounts, annual reports, and websites of patient organisations; payments declared by pharmaceutical manufacturers on their websites and a centralised database (Disclosure UK); declarations of interests by nominated representatives of patient organisations; and responses from patient organisations. Setting: Appraisals of medicines and treatments (technologies) for use in the English and Welsh National Health Service. Participants: 53 patient organisations contributing to 41 NICE technology appraisals published in 2015 and 2016, with 117 separate occasions that a patient organisation contributed to the appraisal of a technology. Main outcome measures: Prevalence of specific interests (that is, funding from manufacturer(s) of a technology under appraisal or competitor products); proportion of specific interests of which NICE's decision making committees were aware; proportion of unknown specific interests for which disclosure was not required by NICE's policy Results: 38/53 (72%) patient organisations had accepted funding from the manufacturer(s) of a technology or a competitor product in the same year that they had contributed to the appraisal of that technology or the previous year. Specific interests were present on 92/117 (79%) occasions that patient organisations contributed to appraisals in 2015 and 2016. NICE's decision making committees were aware of less than a quarter of specific interests (30/144; 21%). For nearly two thirds of the specific interests not known to committees (71/114; 62%), disclosure by patient organisations was not required by NICE's policy. Conclusions: Financial interests are highly prevalent among patient organisations contributing to health technology assessment. NICE should review its disclosure policy to ensure that decision making committees are aware of all relevant interests.